Kinetics of hydrogen adsorption and mobility on Ru nanoparticles supported on alumina: Effects on the catalytic mechanism of ammonia synthesis - Fernández, Camila; Bion, Nicolas; Gaigneaux, Eric M.; Duprez, Daniel; Ruiz, Patricio (Chinese journal of catalysis, 2016)
[Display omitted] •Hydrogen adsorption on large Ru nanoparticles leads to H atoms with high mobility.•On small Ru nanoparticles, H atoms are strongly adsorbed and present low mobility.•H migration to nearby Ru particles occurs via exchange with OH groups of alumina.•Hydrogen transfer from large to small Ru particles promotes the rate of NH3 synthesis.•Broad size distribution of Ru particles causes synergy in the activity and H diffusivity. Relevant findings on hydrogen adsorption and mobility are provided in this work to elucidate the mechanism of low-temperature ammonia synthesis, catalyzed by polydispersed Ru nanoparticles supported on alumina. H/D isotopic exchange technique, complemented by DRIFTS analysis, was applied to study the kinetics of hydrogen adsorption/desorption on metallic Ru and hydrogen diffusivity on alumina, for catalysts presenting different size distributions of Ru nanoparticles. H atoms adsorbed on large Ru nanoparticles present higher mobility and they migrate on alumina via exchange with OH groups. A broad size distribution of Ru nanoparticles leads to synergy in the rate of ammonia synthesis, and also in hydrogen mobility. The mechanism of catalytic cooperation involves transfer of H atoms from large to small nanoparticles, where the reaction rate is promoted. Considering dynamic catalytic processes in the formulation of kinetic models is crucial for a more accurate description of processes and the development of large-scale processes.